Travel behaviour in Saudi Arabia and the role of social factors - Al-Atawi, Attiyah; Saleh, Wafaa (Transport, 2014)
Travel behaviour research indicates that travel decisions are usually influenced by accessibility as well as characteristics of the transport systems. Factors such as travel times, travel costs, waiting times, walking times have the most significant contributions in mode choice and travel decisions. In the case of developing countries however, the most influencing factors for travel behaviour and decisions are the social factors. This is very important for transport modellers and decision makers to realise in order to achieve appropriate design and implementations of various transport policies. The influence of social and economic factors on travel behaviour are discussed and investigated in this paper. In Saudi Arabia, a randomly selected sample of 1220 households was interviewed in the Tabuk city of the Saudi Arabia and data on their socio-economic and trip-making behaviour was obtained. The relative impact of socioeconomic variables on household travel behaviour was discussed and discrete choice models were calibrated. These types of studies can be useful in the development of plans, programs and policies for the improvement of transportation systems in urban areas of the Saudi Arabia and other similar countries in the region. The findings show that the social factors have the most important impact on travel behaviour in Saudi Arabia.First published online: 09 May 2014